THE EFFECT OF SHARIA FINANCIAL LITERACY AND SHARIA FINANCIAL INCLUSION ON THE FINANCIAL MANAGEMENT OF MSMEs IN MEDAN CITY - Nurani, Khadijah; Khairi, Himmatul (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2024)
Financial literacy is something that can overcome the problem of subduing financial inclusion with the aim that finances in Indonesia can increase. Financial inclusion is an effort to encourage the financial system so that it is easy for the public to access to promote good economic growth. This research was conducted to determine the influence of Sharia Financial literacy and Sharia Financial inclusion on the financial management of micro, small and medium enterprises (UMKMs) in Medan City. The data collection method was carried out by distributing questionnaires with a sample of 100 respondents. The data analysis technique used is multiple linear regression and uses the T  and the F test. In addition, classical assumption tests were carried out which included multicholinearity tests, heteroskedasticity tests, autocorrelation tests and normality tests. The results of this study show that Sharia Financial literacy has a positive and significant influence on financial management, Sharia Financial inclusion has a positive and significant influence on the financial management of micro, small and medium enterprises in Medan City and ShariaFinancial literacy and Sharia Financial inclusion have a positive and significant influence on micro-enterprise financial management, SMEs in Medan City